Characteristics of Nata De Taro from “Beneng” Taro Starch Waste with Addition of Various Types of Carbon and Isolated Soy Protein - Hakiki, Dini Nur; Maulani, Tuti Rostianti (Department of Agro-industrial Technology, University of Brawijaya, 2020)
AbstractThe research aims to characterize nata of “Beneng” taro starch waste with addition of various types of carbon and several concentration of Isolated Soy Protein (ISP). The experimental design used was a complete randomized group design with ISP concentrations of 1%, 1.5%, and 2%. “Beneng” taro waste was heated, added with 2% vinegar, then treated with a carbon source of sucrose and glucose 5% and a nitrogen source from the ISP at concentrations of 1%, 1.5%, and 2% and fermented for 13 days. The results showed the combination of glucose with 1% ISP gave the best results and yield of 44.28%, 0.984 cm of thickness was not significantly different from the addition of ZA with a yield of 43.77%, thickness of 1.016 cm. Nata fiber content tends to be higher in the treatment with ZA addition compared to ISP, although it is not significantly different. The value of the white level is getting higher or the nata become brighter in the glucose treatment with ISP and significantly different from other treatments. The addition of ISP has the potential as an alternative for substitution of ZA and tends to increase the brightness of nata color.Keywords: “Beneng” taro, fermentation, isolated soy protein, nata